Thermodynamics of trajectories and local fluctuation theorems for harmonic quantum networks. (23rd December 2015) - Pigeon, Simon; Fusco, Lorenzo; Xuereb, André; Chiara, Gabriele De; Paternostro, Mauro
Abstract: We present a general method to undertake a thorough analysis of the thermodynamics of the quantum jump trajectories followed by an arbitrary quantum harmonic network undergoing linear and bilinear dynamics. The approach is based on the phase-space representation of the state of a harmonic network. The large deviation function associated with this system encodes the full counting statistics of exchange and also allows one to deduce fluctuation theorems (FTs) obeyed by the dynamics. We illustrate the method showing the validity of a local FT about the exchange of excitations between a restricted part of the environment (i.e., a local bath) and a harmonic network coupled with different schemes.